Sistem Pendukung Keputusan Penentuan Prioritas Bantuan Stimulan Perumahan Swadaya Menggunakan Metode SMART - Ongki Firdian Afandi; Anief Fauzan Rozi (Journal of Information System and Artificial Intelligence, 2023)
The self-help home assistance program is an annual work program at the Sleman Regency Public Works Department. In determining the recipient of home self-help assistance at the Sleman district public works service, it is still done manually so that a lot of data is not stored properly and even is lost. In this study, the researcher aims to create a system that can assist in determining the recipients of self-help housing in Sleman district so that data can be well documented and the process of determining beneficiaries does not take time. This study uses the SMART (Simple Multi Attribute Rating Technique) method with an assessment of 13 criteria, namely roof covering damage, roof truss damage, column and ring block damage, brick and wall damage, frame damage, window shutter damage, door leaf damage, substructure damage. , damage to the floor covering, damage to the sloof, damage to the bathroom, damage to the bathroom, damage to drains. Based on the results of the study, it can be concluded that the application of decision-making using the SMART (Simple Multi Attribute Rating Technique) method resulted in a 100% match between manual calculations and the system with 75% test data.